Ximelagatran versus warfarin for prophylaxis of venous thromboembolism in major orthopedic surgery: systematic review of randomized controlled trials - Yoshida, Winston Bonetti; Dib, Regina Paolucci El; Yoshida, Ricardo de Alvarenga; Maffei, Francisco Humberto de Abreu (São Paulo Medical Journal, 2006)
BACKGROUND: Ximelagatran has been recently studied for prophylaxis in surgical orthopedic cases. PURPOSE: We proposed to establish whether in- terventions involving ximelagatran, as compared with warfarin, would increase thromboembolic prophylaxis in patients undergoing major ortho- pedic knee surgery. DATA SOURCE: Studies with random assignment were identified by an electronic search of the medical literature up to 2006. Data were double- entered into the Review Manager software, version 4.2.5. DATA SYNTHESIS: We included three well conducted clinical trials involving 4,914 participants. Sub-groups with two dosages of ximelagatran (24 mg and 36 mg, b.i.d.), were defined. Ximelagatran showed significantly lower frequency of total venous thromboembolism (VTE) than warfarin, but only with the 36-mg dosage (risk relative, RR: 0.72; 95% confidence interval, CI: 0.64-0.81; p < 0.00001). For the 24-mg subgroup, total VTE frequency was similar (RR: 0.86; 95% CI: 0.73-1.01; p = 0.06). No significant differences were shown with either ximelagatran dosage for deep vein thrombosis (DVT), pulmonary embolism, any bleeding or severe bleeding. At the end of the treatment, alanine aminotransferase (ALT) elevation was less frequent in the 24-mg ximelagatran sub-group (RR: 0.33; 95% CI: 0.12-0.91; p = 0.03], but during the follow-up period, the ALT elevation rate was greater in the 36-mg ximelagatran group (RR: 6.97; 95% CI: 1.26-38.50; p = 0.03]. CONCLUSIONS: Ximelagatran appears to be more effective than warfarin when used in higher dosages (36 mg b.i.d.), but at the expense of increased frequency of ALT elevation during the follow-up period.